Case Report: A rare treatable metabolic syndrome (Brown-Vialetto-Van Laere syndrome) masquerading as chronic inflammatory demyelinating polyneuropathy from Saudi Arabia - Kentab, Amal Y.; Alsalloum, Yara; Labani, Mai; Hudairi, Abrar; Hamad, Muddathir H.; Jamjoom, Dima Z.; Alwadei, Ali H.; Alhammad, Reem M.; Bashiri, Fahad A. (Frontiers in Pediatrics, 2024)
Background: Brown-Vialetto-Van Laere (BVVL) syndrome is an extremely rare autosomal recessive progressive motoneuron disease that is caused by a defect in the riboflavin transporter genes SLC52A2 and SLC52A3. BVVL syndrome has a variable age of presentation, and it is characterized by progressive auditory neuropathy, bulbar palsy, stridor, muscle weakness, and respiratory compromise secondary to diaphragmatic and vocal cord paralysis. BVVL syndrome has a poor prognosis in the absence of treatment, including morbidity with quadriparesis and sensorineural hearing loss, with mortality in the younger age group. Early administration of riboflavin is associated with prolonged survival, low morbidity, and reversal of some clinical manifestations.We describe an 18-month-old male infant with progressive pontobulbar palsy, loss of developmental milestones, and a clinical picture suggestive of chronic inflammatory demyelinating neuropathy. A nerve conduction study revealed axonal neuropathy, while molecular analysis revealed a homozygous mutation in one of the riboflavin transporter genes, SLC52A3, confirming BVVL syndrome. The patient needed long-term respiratory support and a gastrostomy tube to support feeding. With high-dose riboflavin supplementation, he experienced moderate recovery of motor function.This report highlights the importance of considering BVVL syndrome in any patient who presents with the clinical phenotype of pontobulbar palsy and peripheral axonal neuropathy, as early riboflavin treatment may improve or halt disease progression, thus reducing the associated mortality and morbidity.